Diversity Of Wildlife At Ruhitpur Union, Keraniganj, Dhaka (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The study was carried out through direct field observation by plot counting; transect line method and interviewing the local people from September 2011 to March 2012. A total of 83 species of wildlife belonging to 18 orders, 34 families and 64 genera was recorded. Of them, 4 (4.82%) species were amphibians, 17 (20.48%) reptiles, 55 (66.27%) birds and 7 (8.43%) mammals. Of the amphibians, 3 (75%) were frogs and rest 1 (25%) was toad. Of the reptiles, 3 (17.65%) were turtles, 7 (41.18%) lizards and 7 (41.18%) were snakes. Of the birds, 30 (54.55%) were passerines and remaining 25 (45.45%) were non-passerines. Regarding the resident status, 44 (80.00%) species of birds were resident and 11 (20.00%) were winter migrants. Of the mammals, 4 (57.13%) were rodents, 1 (14.29%) bats, 1 (14.29%) carnivore and 1(14.29%) insectivore. The relative abundance showed that 16 (20.00%) were very common, 17 (21.18%) common, 22 (25.8854) fairly common and 28 (32.94%) were few. Among the threatened categories, 2 (2.35%) were critically endangered, 3 (3.53%) endangered, 13 (15,29%) vulnerable, 50 (61 18%) lower risk and 15 (17.65%) species were data deficient Some threats were identified as the cause for the declining of the biodiversity i.e. habitat degradation, climate change, over exploitation of agricultural lands. Implementation of conservation and management practice is necessary to protect the diversity of present species and their population in the studied habitatsAsiat. Soc. Bangladesh, Sci. 40(2): 295-308, December 2014